Audesc: Translating Images into Words for Spanish Visually Impaired People - Hernández-Bartolomé, Ana; Mendiluce-Cabrera, Gustavo (Meta, 2004)
AbstractAlthough audiovisual translation is a relatively new field within Translation Studies, it is widening its perspectives to recent areas. Some of them are particularly concerned with minority groups, such as sensory impaired people. Specifically, the blind and visually impaired constitute an unexplored group. In this paper we introduce the system of “audio description,” which translates images into words to make audiovisual products accessible to this special-needs social sector. Since not much literature on the topic is available, we will provide the background and some general procedures for this type of intersemiotic translation. However, our greatest interest will be Audesc, the Spanish audio descriptive project developed by ONCE (the Spanish Organisation for the Blind), mainly applied to the cinema and the theatre. Finally, our paper hints at attaching the audio describer’s role to the audiovisual translator’s.